STRUKTUR DAN KOMPOSISI POHON DI HABITAT BURUNG MALEO (Macrocephalon maleo S. Muller, 1846) DI TANJUNG BINEREAN, DESA MATAINDO - Riyanto Silayar; Hard N. Pollo; Johny S. Tasirin (COCOS, 2017)
ABSTRACT Macrocephalon maleo S. Muller, 1846, an endemic bird species to Sulawesi and classified as Endangered, is now used as flagship species for conservation purpose. Conversion of its habitat, habitat loss and fragmentation, and degraded habitat quality are several suspected factors that impacted the bird population. Its habitat in Tanjung Binerean at Mataindo Village, South Bolaang Mongondow Regency is now suspected to be declined in form of habitat quality. The aims of this research was to analyze Maleo Bird's habitat based on tree structure and composition. The researh was done in Tanjung Binerean at Mataindo Village, South Bolaang Mongondow Regency in June 2017 by Systematic Strip Method. Data were collected from three transects on 25 plots, and were analysed its relative frequency distribution. The result showed that there were 56 tree species that dominated by Alianthus integrifolia (21,23 %), Cananga odorata (12,16 %), Canarium asperum (8,82 %), and Ficus septica (8,32 %). This imply that the Maleo's habitat is now in disturbed condition with the presence of F. septica.Keywords : Macrocephalon maleo, South Bolaang Mongondow Regency, habitat, flagship species, Ficus septica